2020
DOI: 10.1002/cne.24844
|View full text |Cite
|
Sign up to set email alerts
|

Candidates for photic entrainment pathways to the circadian clock via optic lobe neuropils in the Madeira cockroach

Abstract: The compound eye of cockroaches is obligatory for entrainment of the Madeira cockroach's circadian clock, but the cellular nature of its entrainment pathways is enigmatic. Employing multiple‐label immunocytochemistry, histochemistry, and backfills, we searched for photic entrainment pathways to the accessory medulla (AME), the circadian clock of the Madeira cockroach. We wanted to know whether photoreceptor terminals could directly contact pigment‐dispersing factor‐immunoreactive (PDF‐ir) circadian pacemaker n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 82 publications
1
24
0
Order By: Relevance
“…A small set of branches from the DNs innervates the calyces of the mushroom bodies [81] (Figure 5B). The group of LK neurons associated with the medulla [27] has been described in more detail as part of the accessory medulla complex that is a pacemaker region of the circadian clock [91][92][93]. Some of these LK neurons colocalize pigment-dispersing factor (PDF), which is one of the major neuromodulators of the clock in L. maderae and Drosophila [91,93,94].…”
Section: Lk Expression Is In Diverse Types Of Neurons In the Cockroach L Maderae (R Maderae)mentioning
confidence: 99%
“…A small set of branches from the DNs innervates the calyces of the mushroom bodies [81] (Figure 5B). The group of LK neurons associated with the medulla [27] has been described in more detail as part of the accessory medulla complex that is a pacemaker region of the circadian clock [91][92][93]. Some of these LK neurons colocalize pigment-dispersing factor (PDF), which is one of the major neuromodulators of the clock in L. maderae and Drosophila [91,93,94].…”
Section: Lk Expression Is In Diverse Types Of Neurons In the Cockroach L Maderae (R Maderae)mentioning
confidence: 99%
“…The glomeruli of the cockroach AME are densely innervated by GABA-immunoreactive (GABA-ir) processes of the distal tract that connects the AME to distal layers of the medulla where long photoreceptor neurons of the compound eye terminate (Giese et al, 2018a). Thus, it was suggested that the distal tract relays indirect light input as photic entrainment pathway into the circadian clock (Arnold et al, 2020;Petri et al, 2002;Reischig & Stengl, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, GABA-ir neurons belong to different soma groups associated with the AME that innervate glomeruli as well as interglomerular regions of the AME (Arnold et al, 2020;Giese et al, 2018a, b).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, contralaterally projecting clock neurons such as contralateral aPDFMEs are clock outputs connecting the clock to locomotor control centers [ 12 , 46 48 , 39 , 49 52 ]. Thus, it was suggested that contralaterally projecting aPDFMEs control locomotor activity rhythms, while ipsilaterally remaining aPDFMEs control sleep/rest in the Madeira cockroach [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%